A satellite cell‐specific knockout of the androgen receptor reveals myostatin as a direct androgen target in skeletal muscle. Issue 7 (26th March 2014) - Dubois, Vanessa; Laurent, Michaël R.; Sinnesael, Mieke; Cielen, Nele; Helsen, Christine; Clinckemalie, Liesbeth; Spans, Lien; Gayan‐Ramirez, Ghislaine; Deldicque, Louise; Hespel, Peter; Carmeliet, Geert; Vanderschueren, Dirk; et al.
ABSTRACT: Androgens have well‐established anabolic actions on skeletal muscle, although the direct effects of the androgen receptor (AR) in muscle remain unclear. We generated satellite cell‐specific AR‐knockout (satARKO) mice in which the AR is selectively ablated in satellite cells, the muscle precursor cells. Total‐limb maximal grip strength is decreased by 7% in satARKO mice, with soleus muscles containing ~10% more type I fibers and 10% less type IIa fibers than the corresponding control littermates. The weight of the perineal levator ani muscle is markedly reduced (–52%). Thus, muscle AR is involved in fiber‐type distribution and force production of the limb muscles, while it is a major determinant of the perineal muscle mass. Surprisingly, myostatin (Mstn), a strong inhibitor of skeletal muscle growth, is one of the most androgen‐responsive genes (6‐fold reduction in satARKO) through direct transcription activation by the AR. Consequently, muscle hypertrophy in response to androgens is augmented in Mstn‐knockout mice. Our finding that androgens induce Mstn signaling to restrain their own anabolic actions has implications for the treatment of muscle wasting disorders.—Dubois, V., Laurent, M. R., Sinnesael, M., Cielen, N., Helsen, C., Clinckemalie, L., Spans, L., Gayan‐Ramirez, G., Deldicque, L., Hespel, P., Carmeliet, G., Vanderschueren, D., and Claessens, F. A satellite cell‐specific knockout of the androgen receptor reveals myostatin as a direct androgen target in skeletal muscle. FASEB J . 28, 2979–2994 (2014). www.fasebj.org